Isolation and Characterization of Plant Growth Promoting Endophytic Bacteria From Peganum Harmala L - Babar, Zainab Zobala; Younis, Tahira; Shinwari, Zabta Khan (Biological and Clinical Sciences Research Journal, 2025)
Endophytes are increasingly recognised as a sustainable alternative to chemical fertilisers and pesticides in modern agriculture. Syrian rue (Peganum harmala L.) is a medicinal plant of importance, yet no prior studies have reported the isolation of bacterial endophytes from its stem. Objective: To isolate, identify, and evaluate the plant growth-promoting and biocontrol potential of bacterial endophytes from the stem of Peganum harmala. Methods: This experimental study involved the isolation of six bacterial endophytes from the stem of P. harmala. Strains were identified using 16S rRNA gene sequencing, which revealed the presence of Bacillus stercoris, B. tropicus, Staphylococcus simiae, Cladifontibacillus erzurumensis, B. subtilis, and B. mobilis. Biochemical characterisation was performed to assess phosphate solubilization, siderophore production, ammonia and HCN production, hydrolytic enzyme activities (cellulase, protease, and pectinase), and indole-3-acetic acid (IAA) production with and without tryptophan supplementation. Antifungal activity against Aspergillus niger and Rhizoctonia solani was tested. Furthermore, the impact of bacterial inoculation on tomato seed germination and seedling growth (Solanum lycopersicum) was evaluated under controlled conditions. Results: B. mobilis demonstrated the strongest phosphate solubilization ability (4.0 ± 0.2 mm), while both B. tropicus and B. mobilis showed superior siderophore, ammonia, and HCN production. All isolates exhibited diverse hydrolytic enzyme activities, with B. stercoris showing the highest cellulase activity (13.8 ± 0.4 mm), B. tropicus demonstrating the greatest protease activity (7.6 ± 0.5 mm), and both B. stercoris and C. erzurumensis producing prominent pectinase zones (24 ± 0.3 mm). IAA production ranged between 4.9 and 5.9 µg/mL without tryptophan and 10.6 and 12.8 µg/mL with supplementation. Except for S. simiae, all isolates exhibited strong antifungal activity. Among plant assays, B. tropicus notably enhanced tomato seed germination compared to the uninoculated control. Conclusion: The identified endophytic bacterial strains, particularly B. tropicus and B. mobilis, demonstrated significant plant growth-promoting and antifungal properties. These strains hold potential as eco-friendly biofertilizers and biocontrol agents, offering sustainable alternatives to chemical inputs in agriculture.